Concept and canons of fasting in Ayurveda - H Shripathi Adiga (Journal of Fasting and Health, 2013)
Ayurveda, manoeuvres mankind to head a healthy life in order to pursue four-fold bliss. With a view to combat physical and mental annoyances, classics have explicated two-fold therapeutic modalities; langhana/depletion and brihmana/nourishing. Upavasa /fasting is one among ten depletion therapies explained. It is envisioned at all three levels of Ayurvedic therapies- rational/objectively planned, psychological, and spiritual. Fasting is reckoned to be refraining from all forms of food intake for a given period, under supervision of a qualified physician. Acharya Charaka advocates fasting in diseases of milder intensity, in those due to aama (metabolic toxin), after purificatory procedures. Fasting person should avoid beautifying oneself, day sleep, sexual acts, and feasting prior and ulterior to fasting. Fasting is contraindicated in very young, elderly, emaciated, pregnant lady, and shortly after strenuous exercise. The principle avers that fasting kindles metabolic/digestive fire which, in absence of food, brings about paachana of vitiated doshas, thereby riposting health. Sound fasting ensues proper elimination of excretory wastes, clear belch, sweat, and taste for food. Benefits of fasting include lucidity of sense organs, lightness of body and mind, control of diseases, and enthusiasm. Yoga Shastra describes fasting with respect to three levels of food: physical, impressions, and associations and a means to unite three bodies: astral, physical, and causal. Ayurveda thus advocates fasting depending upon the dosha, agni, vaya, kala, and bala of the individual, as a preventive as well as therapeutic modality.